2018
DOI: 10.21815/jde.018.105
|View full text |Cite
|
Sign up to set email alerts
|

An International Survey of Female Dental Students’ Perceptions About Gender Bias and Sexual Misconduct at Four Dental Schools

Abstract: As women enter the dental profession in increasing numbers in North America and around the world, the questions of how they perceive their environment and what kind of barriers they face are important subjects to be addressed. The aim of this study was to assess and compare women dental students’ perceptions of bias in their environment and experiences of sexual misconduct at one dental school in each of four countries. In spring 2017, 1,293 female students at four dental schools in the U.S., Bulgaria, Brazil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
1
20
1
1
Order By: Relevance
“…(Bhatia, 2019; Qiu et al, 2020) Probably, this COVID19 adds to the pre-existing stressors. (Bhatia, 2019; Ivanoff et al, 2018) The significance of gender, was lost in multivariate analysis except for PSS High to low stress comparison, where female endodontists are twice likely to experience high stress than their male counterparts. However, in CPDI, there is no significance.…”
Section: Discussionmentioning
confidence: 99%
“…(Bhatia, 2019; Qiu et al, 2020) Probably, this COVID19 adds to the pre-existing stressors. (Bhatia, 2019; Ivanoff et al, 2018) The significance of gender, was lost in multivariate analysis except for PSS High to low stress comparison, where female endodontists are twice likely to experience high stress than their male counterparts. However, in CPDI, there is no significance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a 2014 study found that almost half of the interviewed people reported having witnessed some situation of gender discrimination in the clinical background 18 . Recent studies have shown that this scenario of gender discrimination has not yet changed within educational institutions in which students, staff, and teachers are still afraid to report episodes and do not know how to deal with these occurrences adequately 12 . All these accumulated situations impact the possibility of promotion within institutions, salaries, hiring, and financing for the development and leadership of research lines and scientific production of women 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, women tend to not appear expressively in positions of first or last author in scientific publications 6,11 . Considering inequalities and prejudices faced by women, analyzing scientific production data is necessary and important 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…20 It is now estimated that 50% of the global dental workforce under the age of 35 are female. 21 In the uK this feminising trend was first observed in 2004. Since then, the net number of female registrants to the GDC has increased.…”
Section: Women In Dentistrymentioning
confidence: 97%